2015
DOI: 10.1021/ac504818s
|View full text |Cite
|
Sign up to set email alerts
|

Newly Fabricated Magnetic Lanthanide Oxides Core–Shell Nanoparticles in Phosphoproteomics

Abstract: Metal oxides show high selectivity and sensitivity toward mass spectrometry based enrichment strategies. Phosphopeptides/phosphoproteins enrichment from biological samples is cumbersome because of their low abundance. Phosphopeptides are of interest in enzymes and phosphorylation pathways which lead to the clinical links of a disease. Magnetic core-shell lanthanide oxide nanoparticles (Fe3O4@SiO2-La2O3 and Fe3O4@SiO2-Sm2O3) are fabricated, characterized by SEM, FTIR, and EDX and employed in the enrichment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Cellulose–SiO 2 –IMAC–Sm 3+ (Najam‐ul‐Haq, Jabeen, Shafiq, Sajid, & Saba, ), SiO 2 –La 2 O 3 composite (Jabeen et al, ) and Fe 3 O 4 @Sm 2 O 3 core–shell nanocomposites (Jabeen et al, ) were synthesized using the reported protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Cellulose–SiO 2 –IMAC–Sm 3+ (Najam‐ul‐Haq, Jabeen, Shafiq, Sajid, & Saba, ), SiO 2 –La 2 O 3 composite (Jabeen et al, ) and Fe 3 O 4 @Sm 2 O 3 core–shell nanocomposites (Jabeen et al, ) were synthesized using the reported protocols.…”
Section: Methodsmentioning
confidence: 99%
“…are often used to enrich phosphopeptides. [167] For example, Zhang's group [168] synthesized adenosineÀ Ti 4 + functionalized mesoporous graphene oxide nanospheres (MG@mSiO2À ATPÀ Ti 4 + ) to selectively extract phosphorylated peptides from complex biological samples. As a result, MG@mSiO2À ATPÀ Ti 4 + has excellent surface properties, good hydrophilicity, size exclusion effect, excellent sensitivity and selectivity to phosphopeptides.…”
Section: Immobilized Metal Ions For the Enrichment Of Phosphopeptidesmentioning
confidence: 99%
“…Aside from the common metal oxides, lanthanide oxides are also explored to capture phosphoproteins/phosphopeptides. Jabeen et al prepared two magnetic core–shell lanthanide oxides of Fe 3 O 4 @SiO 2 –La 2 O 3 and Fe 3 O 4 @SiO 2 –Sm 2 O 3 recently, the successive hydroxyl groups on which can form bidentate ligand coordination with phosphopeptides . Both of the magnetic lanthanide oxides exhibited high selectivity when using β‐casein/bovine serum albumin (BSA) peptide mixture at ratio of 1:8500 as test sample, as well as high sensitivity of 0.001 fmol, owing to the affinity ability of electrostatic, covalent, and bidentate coordination provided by Sm/La (III).…”
Section: Nanomaterials In Phosphoproteomicsmentioning
confidence: 99%